Kyrgyzstan at a Crossroads: Democracy and the Struggle for Human Rights - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2024)
This paper examines the current human rights situation in Kyrgyzstan, a Central Asian country with a complex history and a challenging human rights record. Despite gaining independence in 1991 and making strides towards democratization, Kyrgyzstan continues to grapple with serious human rights issues. This analysis focuses on three critical areas: the use of torture by law enforcement and security services, restrictions on free expression, and interference with the freedom of association. This paper highlights the gap between the government's commitments to human rights reforms and the reality of persistent abuses and systemic challenges. The study finds that these human rights abuses are not isolated incidents but are indicative of deeper societal and governmental issues that hinder Kyrgyzstan's democratic development. The paper concludes by emphasizing the need for comprehensive reforms and continued domestic and international efforts to address these human rights challenges.